التخطيط الاستراتيجي وعلاقته بالفعالية التنظيمية في المؤسسة الخدماتية د - بلكرم قطر الندى (Universty Of El-oued جامعة الوادي, 2024)
الملخص: سعت هاته الدراسة إلى محاولة معالجة موضوع التخطيط الاستراتيجي وعلاقته بالفعالية التنظيمية، كأحد المواضيع المهمة التي يتم دراستها في مجال إدارة المؤسسات والاعمال، وخاصة في مجال التنظيم والعمل محاولين تقصي الواقع السوسيو-تنظيمي لعملية التخطيط الاستراتيجي في المؤسسة الخدماتية وقد ركزت هاته الدراسة على مدى علاقة وارتباط التخطيط الاستراتيجي والفعالية التنظيمية وكيفية تحقيقها في المؤسسات الخدماتية، ولقد قمنا بتقسيم هاته الدراسة إلى جانبيين نظري وميداني. جانب نظري: حاولنا من خلاله، توضيح الإطار النظري والتصوري للدراسة، بما تضمنته من إشكالية وفرضيات، واهداف لدراسة أهمية ومبررات لاختيار الموضوع، إضافة الى تحديد المفاهيم وعرض الدراسات السابقة وفي الأخير تعرضنا إلى المقاربة النظرية تم فيها توضيح مختلف المداخل النظرية المفسرة للموضوع، ورصد ما قدمته من مبادئ وأفكار في الفكر التنظيمي الكلاسيكي والنيو كلاسيكي والحديث والتي صبت في مجملها على تلاقي دلالات التخطيط الاستراتيجي والفعالية التنظيمية في الكثير من الجوانب. جانب ميداني: حاولنا من خلاله إتباع استراتيجية منهجية، متكاملة الهدف منها تشخيص الواقع الفعلي لمتغيري الدراسة و الاقتراب أكثر من فهم المؤسسة الخدماتية متخذين مستشفى كوبا لطب العيون كنموذج، و قد اشتملت هاته الاستراتيجية على جملة من الإجراءات المنهجية بحيث اعتمدنا على المنهج الوصفي باختيار عينة المسح الشامل شملت 110 عامل بنسبة 100 بالمئة من مجتمع الدراسة، كما اعتمدنا على تقنية الاستمارة كأداة أساسية في جمع البيانات الميدانية على اعتبارها الأداة الأكثر موائمة للبحث العلمي، علاوة على تحليل و تفسير البيانات الميدانية و مناقشتها في ضوء الفرضيات، و أخيرا قمنا بطرح بعض التوصيات و الافاق التي اثارتها الدراسة، حيث في الأخير تم التوصل الى بعض النتائج نذكر منها: يساعد التخطيط الاستراتيجي في المؤسسة الخدمية على زيادة الفعالية التنظيمية، وذلك عن طريق تحقيق التوجه الاستراتيجي، تحسين التنظيم والتنسيق، تعزيز التوجيه واتخاذ القرار، تعزيز الرؤية المشتركة والتواصل، وتحقيق التكيف والتطوير مما يعزز التخطيط الاستراتيجي الرؤية المشتركة ويساعد على تحسين التنظيم والاتصالات داخل المؤسسة، مما يؤدي إلى زيادة الفعالية التنظيمية وتحقيق الأهداف المحددة. المناخ التنظيمي يلعب دورا حاسما في تعزيز رضا الموظفين وتحفيزهم، وتعزيز التعاون والابتكار، وتحقيق الالتزام والانتماء، وتقليل التوتر والصراعات، مما ينبغي للمؤسسة الاهتمام ببناء مناخ تنظيمي إيجابي من خلال تعزيز القيم والثقافة المناسبة، وتحفيز التواصل الفعّال والتعاون، وتقديم فرص التطوير والمشاركة للموظفين، بشكل عام التخطيط الاستراتيجي يعزز الشفافية والتوجيه والتفاعل في المؤسسة مما يؤدي الى تحسين المناخ التنظيمي للعمل والأداء العام ويعمل كأداة مهمة لتعزيز المناخ التنظيمي الإيجابي وتحقيق النجاح المستدام للمؤسسة الكفاءة التنظيمية تلعب دورا حاسما في تعزيز أداء المؤسسة الخدمية وتحقيق الاستدامة والنجاح في بيئة العمل المتنوعة والمتغيرة وينبغي للمؤسسة الاستثمار في تحسين الكفاءة التنظيمية من خلال تنظيم الهيكلية والعمليات وتعزيز التواصل والتعاون بين الموظفين وتحديد المسؤوليات ومراقبة الأداء، بالتالي يمكن القول إن التخطيط الاستراتيجي والكفاءة التنظيمية يتعاونان معا لتعزيز أداء المؤسسة وتحقيق الأهداف المحددة. بشكل عام التخطيط الاستراتيجي يمكن أن يؤثر بشكل إيجابي على الرضا الوظيفي من خلال توجيه الأهداف وتشجيع المشاركة وتوفير فرص التطوير وتحقيق توازن العمل والحياة الشخصية وفي المقابل يمكن أن يؤثر الرضا الوظيفي على التخطيط الاستراتيجي من خلال زيادة التفاني والالتزام بالعمل وتعزيز التعاون والابتكار وتقليل معدل التحول والاستقرارين الفريق العامل بالتالي يمكن القول إن الرضا الوظيفي والتخطيط الاستراتيجي يتعاونان معا لتحقيق الأهداف المرجوة لكل مؤسسة. يساعد التحليل الاستراتيجي الجيد في المؤسسة الخدماتية القدرة على فهم البيئة الداخلية والخارجية واتخاذ القرارات المبنية على أسس قوية، وتحسين الأداء وتحقيق التفوق التنافسي والنمو ويساعد في رؤية أوضح للمؤسسة وتحقيق تنمية مستدامة ويمكن أن يكون أداة فعالة للتخطيط والتنفيذ والمراقبة والتقييم في المؤسسة. تشير الأبحاث إلى وجود علاقة إيجابية وقوية بين التخطيط الاستراتيجي والفعالية التنظيمية في المؤسسة، عندما يتم تطبيق التخطيط الاستراتيجي بشكل مناسب، يتم تحقيق توجيه واضح للمؤسسة وتحديد الأهداف والاستراتيجيات اللازمة لتحقيقها وبالتالي يؤدي ذلك إلى تحسين الكفاءة والفعالية في تنفيذ العمليات التنظيمية واتخاذ القرارات. بالإضافة إلى ذلك يساهم التخطيط الاستراتيجي في تعزيز التنظيم والتنسيق بين مختلف أقسام ووحدات المؤسسة وتعزيز التواصل وتبادل المعلومات بين الأعضاء، هذا يؤدي إلى تحسين التنظيم الداخلي وتعزيز قدرة المؤسسة على التكيف مع التحولات البيئية والتحديات الخارجية. باختصار يمكن القول إن التخطيط الاستراتيجي يلعب دوراً حاسماً في تحقيق الفعالية التنظيمية في المؤسسة ويساعد في توجيه الأهداف والاستراتيجيات وتحسين التنظيم الداخلي وتعزيز الأداء العام للمؤسسة. Résumé : فرنسية أو انجلزية This study sought to try to address strategic planning and Its relationship to organizational effectiveness as one of the Important topics being studied in the field of enterprise management and business, especially in the field of organization and work trying to Investigate the socio-organizational reality of the strategic planning process In the service Institution. This study focused on the relevance and relevance of strategic planning and organizational effectiveness and how they are achieved in service institutions. We divided this study into two theoretical and field aspects. Theoretical aspect : we tried to clarify the theoretical and conceptual framework of the study, with Its problematic and hypothetical objectives and objectives to examine the Importance and justification of the choice of the topic, in addition to defining concepts and presenting previous studies, we were exposed to the theoretical approach In which the various theoretical entry points of the topic were clarified. And monitoring its principles and ideas In classical, neo-classical and modern organizational thinking, which as a whole encompassed the convergence of strategic planning connotations and organizational effectiveness In many respects. Field aspect : We tried to pursue a systematic strategy, Integrated with the aim of diagnosing the actual reality of study variants and getting closer to the institution’s understanding of service by taki”g Cuba Ophthalmology Hospital as a model, this strategy Incl’ded a series of methodological measures, so that we adopted the descriptive curriculum by selecting a comprehensive survey sample of 110 workers with 100% of the study community. And relied on the form’s technique as an’essential tool In collecting field data as the most compatible tool for scientific research, as well as analysis and Interpretation of field data and discussion In light of hypotheses and finally we put forward some of the recommendations and prospects that the study raised, In the latter, some results have be”n reached, including : -Strategic planning in the service enterprise helps to Increase organizational effectiveness by achieving strategic direction, Improving organization and coordination, enhancing guidance and decision-making, promoting common vision and communication, and achieving adaptation and development, thereby enhancing strategic planning common vision and helping to Improve organization and communication within the organization, thereby increasing organizational effectiveness and achieving set goals. -Organizational climate plays a crucial role In promoting staff satisfaction and motivation and promoting cooperation and Innovation, achieving commitment and belonging, and reducing tension and conflicts, which should focus on building a positive organizational climate through the promotion of appropriate values and culture In general, strategic planning promotes transparency, guidance and Interaction in the organization, improving the organizational climate of work and public performance and serving as an Important tool for promoting a posi”Ive organizational climate and achieving the organization’s sustainable success. -Organizational efficiency plays a crucial role In enhancing the enterprise’s service performance and achieving sustainability and success in a diverse and changing working environment. The organization should invest in improving organizational efficiency through structural and operational organization, enhanced communication and collaboration among staff, identification of responsibilities and performance control. Therefore, it can be argued that strategic planning and organizational efficiency work together to enhance the enterprise’s performance and achieve the goals set. -Overall strategic planning can positively affect job satisfaction by guiding goals, encouraging participation, providing development opportunities, balancing work and personal life. Conversely, job satisfaction can affect strategic planning by Increasing dedication and commitment to work, promoting collaboration and Innovation, reducing the rate of transformation and stability of the working group. Therefore, job satisfaction and strategic planning can be said to work together to achieve the desired goals of each organization. Good strategic analysis In a service enterprise helps the ability to understand the internal and external environment and make decisions based on strong foundations, Improve performance, achieve competitive excellence and growth and help In a clearer vision of the enterprise and achieve sustainable development and can be an effective tool for planning, implementation, monitoring and evaluation In an enterprise. -Research indicates a positive and strong relationship between strategic planning and organizational effectiveness In an enterprise. When strategic planning is appropriately applied, clear guidance is achieved for the organization and the goals and strategies needed to achieve it are defined. This improves efficiency and effectiveness In the implementation of organizational processes and decision-making. -In addition, strategic planning contributes to enhancing organization and coordination between the various sections and units of the organization, and enhancing communication and Information exchange among members. This Improves internal organization and enhances the enterprise’s ability to adapt to environmental transformations and external challenges. -In short, strategic planning can be said to play a crucial role In the organization’s organizational effectiveness. Helps guide goals and strategies, improve internal organization and enhance the organization’s overall performance
دراسة ميدانية في مستشفى كوبا لطب العيون ولاية الوادي
أطروحة دكتوراه تخصص: علم الاجتماع تنظيم وعمل في العلوم الإنسانية والاجتماعية
Keywords: التخطيط ، التخطيط الاستراتيجي، الفعالية التنظيمية، المؤسسة الخدماتية; Planning; strategic planning; organizational effectiveness; service organization